Hydraulic performance and wave transmission through pile-rock breakwaters. (15th December 2020) - Le Xuan, Tu; Tran Ba, Hoang; Le Manh, Hung; Do Van, Duong; Minh Nguyen, Nguyet; Wright, David P.; Bui, Van Hieu; Mai, Son T.; Tran Anh, Duong
Abstract: In recent years coastal erosion in the Vietnamese Mekong Delta (VMD) is occurring at a rapid rate which is leading to considerable damage of infrastructure and the human-made environment. Various solutions have been proposed to protect the coastline in the VMD including Pile-Rock breakwaters (PRBWs). PRBWs have several advantages that make them particularly applicable to the coast of West Ca Mau and the Mekong Delta. The focus of this study is to test PRBW efficiency in the VMD by evaluating a physical experimental model followed by evaluation of observations in the field from the Ca Mau province. A series of experiments were undertaken to build an empirical formula of the wave transmission coefficient. The results show that the PRBW structure works effectively in the case of emergence when the wave transmission coefficient Kt is between 0.3 and 0.4 but in this case the wave reflection coefficient is quite large (i.e. Kr of 0.45–0.6). The experimentally obtained and measured transmission coefficient Kt show strong agreement. The analytical results show that a PRBW dissipates most of the energy for short periodic waves, however long periodic waves can still be transmitted through the PRBW. The PRBW shows significant advantages over other styles of breakwaters including an increased potential to reduce erosion, high stability, and a reduced deadweight of construction materials. These advantages mean that PRBWs have a great potential to aid restoration of mangrove forests that are sheltered behind the breakwater in the VMD region. Highlights: Building physical model to test wave transmission, wave reflection and hydraulic performance. Constructing real breakwater construction at the site in coastal area in Ca Mau province, Vietnam. Comparing the results of wave transmission from physical model and measuring from real construction. Establishing the empirical formula of wave transmission coefficient.